Combined Prayer for Surgeons During Medical Operations: A Maqasid al-Shari'ah Perspective - Muhammad Ridwan; Rahmadi; Mustajab, Muhammad; Shaukat, Muhammad Awais; Qadarsih.B, Fitri (Program Studi Perbandingan Mazhab Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, 2025)
This research is motivated by the importance of maqasid al-shari'ah as a foundation in establishing Islamic law, particularly in responding to social dynamics such as the implementation of combined prayer (salat jamak) by surgeons during operations. The research problem addressed is how the implementation of combined prayer for surgeons during operations is viewed from a maqasid al-shari'ah perspective. This study employs a qualitative methodology with a library research approach examining relevant literature. The research findings indicate that combining prayers is permissible for physicians in surgical conditions requiring extended time, emergency situations, or intensive preparation, in accordance with Islamic jurisprudential provisions such as jam' taqdim and jam' ta'khir. The application of combined prayer is valid as long as legitimate legal excuses ('udhr shar'i) exist, however, a casual attitude must be avoided as scholars unanimously prohibit combining prayers without religiously justified reasons.